Pengaruh Dana Alokasi Umum, Dana Alokasi Khusus, dan Pendapatan Asli Daerah Terhadap Indeks Pembangunan Manusia Dengan Belanja Modal Sebagai Variabel Mediasi pada Pemerintah Kabupaten/Kota di Provinsi Kalimantan Barat - Pratama, Nanda Saputra; Hamzani, Umiaty; Muhsin, Muhsin; Rusliyawati, Rusliyawati; Karpriana, Angga Permadi (Journal of Innovation in Management, Accounting and Business, 2025)
This study aims to test and prove empirically the effect of General Allocation Fund (DAU), Special Allocation Fund (DAK) and Regional Original Revenue (PAD) to Human Development Index (HDI) with Capital Expenditures as intervening variables in districts or cities of West Kalimantan Province. The population in this research were 12 districts and 2 cities in the Province of West Kalimantan in 2019-2023. The sampling method used was purposive sampling. Data analysis technique used in this study is path analysis. SPSS 25 tool is used for data analysis. The results showed that the General Allocation Fund has a negative and significant effect on the Human Development Index, the Special Allocation Fund has no effect on the Human Development Index. Regional Original Revenues has a positive and significant effect on the Human Development Index. General Allocation Fund has a positive and significant effect on the Capital Expenditure and Special Allocation Fund has no significant effect on the Capital Expenditure. Regional Original Revenue has a positive and significant effect on Capital Expenditure. Capital Expenditure has a positive effect on the Human Development Index and Capital Expenditure are not able to mediate the influence of General Allocation Fund and Special Allocation Fund on the Human Development Index. Regional Original Revenue Capital Expenditure have an significant effect on the Human Development Index which is mediated by Capital Expenditure.